2021
DOI: 10.1200/jco.2021.39.15_suppl.e16186
|View full text |Cite
|
Sign up to set email alerts
|

Association between antibiotic exposure and survival in patients with hepatocellular carcinoma treated with nivolumab.

Abstract: e16186 Background: Nivolumab, an immune checkpoint inhibitor, has improved the outcomes of patients with hepatocellular carcinoma (HCC). It is approved for HCC patients previously treated with sorafenib. Outcomes have been reported in previous studies, in malignancies other than HCC, to be worse when patients have been exposed to antibiotics while receiving immune checkpoint inhibitors. We aimed to evaluate the effects of antibiotics on survival in HCC patients treated with nivolumab. Methods: We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Indeed, recent evidence supports a negative association between ABT and clinical outcomes in cancer patients treated with TKIs, 17 , 24 chemotherapy 31 and ICI therapy. 13 , 19 , 20 , 23 , 35 While concomitant therapy with antibiotics and epidermal growth factor receptor (EGFR)-TKIs in patients with advanced non-small cell lung cancer (NSCLC) was associated with shorter PFS, there were no changes in ORR or DCR in another study. 24 In patients with metastatic renal cell carcinoma (mRCC) treated with VEGF-targeting therapies among others, antibiotic users had a shorter PFS and lower ORR compared to antibiotic nonusers, while OS was not negatively impacted by ABT in the group of patients receiving anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent evidence supports a negative association between ABT and clinical outcomes in cancer patients treated with TKIs, 17 , 24 chemotherapy 31 and ICI therapy. 13 , 19 , 20 , 23 , 35 While concomitant therapy with antibiotics and epidermal growth factor receptor (EGFR)-TKIs in patients with advanced non-small cell lung cancer (NSCLC) was associated with shorter PFS, there were no changes in ORR or DCR in another study. 24 In patients with metastatic renal cell carcinoma (mRCC) treated with VEGF-targeting therapies among others, antibiotic users had a shorter PFS and lower ORR compared to antibiotic nonusers, while OS was not negatively impacted by ABT in the group of patients receiving anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 16–19 Mice with a favourable composition of the commensal microbiome experienced a greater therapeutic activity from ICI therapy. 19 , 20 While modulation of the gut microbiome by fecal microbiota transplant promoted response to ICIs in immunotherapy-refractory melanoma patients, 21 , 22 ABT was associated with shorter survival in patients with different cancer types treated with ICIs 16 , 23 and TKIs. 17 , 24 Patients with advanced chronic liver disease (ACLD) commonly suffer from intestinal dysbiosis and bacterial translocation, which may promote immune dysfunction via the gut–liver axis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who received antibiotics had a shorter median overall survival than those who did not ( P = 0.04). This suggests that patients with HCC receiving nivolumab have worse survival rates if they receive antibiotics, and that antibiotics should be used carefully during ICI treatments ( 75 ). In some other tumor types, multiple clinical trials have also demonstrated that early exposure to antibiotics was associated with poorer outcomes and reduced clinical benefits following ICI treatment, such as worse overall survival and increased disease refractory risk ( 76 , 77 ).…”
Section: Antibiotics In Hccmentioning
confidence: 99%
“…antibiotics should be used carefully during ICI treatments (75). In some other tumor types, multiple clinical trials have also demonstrated that early exposure to antibiotics was associated with poorer outcomes and reduced clinical benefits following ICI treatment, such as worse overall survival and increased disease refractory risk (76,77).…”
Section: Cetobacterium ↓mentioning
confidence: 99%
“…[16][17][18][19] Mice with a favourable composition of the commensal microbiome experienced a greater therapeutic activity from ICI therapy. 19,20 While modulation of the gut microbiome by fecal microbiota transplant promoted response to ICIs in immunotherapy-refractory melanoma patients, 21,22 ABT was associated with shorter survival in patients with different cancer types treated with ICIs 16,23 and TKIs. 17,24 Patients with advanced chronic liver disease (ACLD) commonly suffer from intestinal dysbiosis and bacterial translocation, which may promote immune dysfunction via the gut-liver axis.…”
Section: Introductionmentioning
confidence: 99%